2019
DOI: 10.1080/21691401.2019.1616553
|View full text |Cite
|
Sign up to set email alerts
|

Oral delivery of indinavir using mPEG-PCL nanoparticles: preparation, optimization, cellular uptake, transport and pharmacokinetic evaluation

Abstract: Introduction: Indinavir (IDV) is a potent HIV protease inhibitor used in the treatment of human immunodeficiency virus (HIV). IDV is a weak base with limited aqueous solubility in its unprotonated form; therefore, solubility of IDV in the gastrointestinal tract fluids is the rate-limiting step of its absorption and onset of action. However, in many cases, drugs are not absorbed well in the gastrointestinal tract; polymer nanoparticles were recognized as an effective carrier system for drug encapsulation and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Several macromolecular structures are being explored as DDS [3,4]. Among them, polymeric nanoparticles (NPs) are considered one of the most promising nanocarriers for use in oncology [5,6,7,8,9,10]. Their building blocks are biodegradable and biocompatible, and their release profiles can be modulated by the polymeric structure itself.…”
Section: Introductionmentioning
confidence: 99%
“…Several macromolecular structures are being explored as DDS [3,4]. Among them, polymeric nanoparticles (NPs) are considered one of the most promising nanocarriers for use in oncology [5,6,7,8,9,10]. Their building blocks are biodegradable and biocompatible, and their release profiles can be modulated by the polymeric structure itself.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, revealing the in vivo fate of PEG-PCL polymers is crucial for its medical application. To date, pharmacokinetic differences in vivo between small molecular drugs and PEG-PCL loaded particles have been extensively studied (Feng et al, 2012;Wang et al, 2014;Manjili et al, 2018;Kurd et al, 2019). However, in vivo fate studies of triblock polymers such as PCL-PEG-PCL or PEG-PCL-PEG have not been reported, only a few studies have This research was supported by the National Natural Science Foundation of China (Grant No.…”
Section: Pharmacokinetics Of Peg-pclmentioning
confidence: 99%
“…The brain uptake clearance of Idv delivered orally via Idv-NEs and lactoferrin-treated Idv-NEs were 393- and 420-times higher compare to the free drug [ 79 ]. Likewise, the oral delivery of Idv loaded methoxypoly (ethyleneglycol)-poly (e-caprolactone) (mPEG-PCL) nanoparticle in the rat showed increased bioavailability of the drug in plasma compared to the Idv solution [ 80 ]. The assembly of multiple retroviral drugs into a single NEs carrier system may empower the effective treatment of HIV infection.…”
Section: Essential Oil-based Nes/mes Antiviral and Drug Delivery Systmentioning
confidence: 99%